Hyper Gaussian windows with fractional wavefronts - Ojeda-Castaneda, Jorge; Ledesma, Sergio; Gomez-Sarabia, Cristina Margarita (Photonics Letters of Poland, 2013)
For reducing the impact of focus errors on the modulation transfer function (MTF), we explore the use of fractional phase power masks combined with either sub Gaussian windows, or super Gaussian windows. We present a sub Gaussian mask combined, with an asymmetric fractional phase profile, which reduces both the variations of the MTF vs. focus errors and the oscillations of the MTF around its tendency curve. However, this mask also reduces the light throughput by a factor of two. Full Text: PDF References M. Mino, Y. Okano, "Improvement in the OTF of a Defocused Optical System Through the Use of Shaded Apertures", Appl. Opt. 10, 2219-2225 (1971). CrossRef J. Ojeda-Castaneda, L. R. Berriel Valdos and E. L. Montes, "Line-spread function relatively insensitive to defocus", Opt. Lett. 8, 458-460 (1983). CrossRef J. Ojeda-Castaneda, L. R. Berriel-Valdos, E. Montes, "Ambiguity function as a design tool for high focal depth", Appl. Opt. 27, 790-795, (1988). CrossRef E. R. Dowski, T. W. Cathey, "Extended depth of field through wave-front coding", Appl. Opt. 34, 1859-1865 (1995). CrossRef N. George, W. Chi, "Extended depth of field using a logarithmic asphere", J. Opt. A - Pure Appl. Opt. 5, 157-163 (2003). CrossRef A. Sauceda and J. Ojeda-Castaneda, "High focal depth with fractional-power wave fronts", Opt. Lett. 29, 560-562 (2004). CrossRef A. Castro and J. Ojeda-Castaneda, "Asymmetric Phase Masks for Extended Depth of Field", Appl. Opt. 43, 3474-3479 (2004). CrossRef S. Mezouari, G. Muyo, A. R. Harvey, "Circularly symmetric phase filters for control of primary third-order aberrations: coma and astigmatism", J. Opt. Soc. Am. A 23, 1058-1062 (2006). CrossRef J. Ares García, S. Bará, M. Gomez García, Z. Jaroszewicz, A. Kolodziejczyk, and K. Petelczyc, "Imaging with extended focal depth by means of the refractive light sword optical element", Opt. Exp. 16, 18371 (2008). CrossRef J. Ojeda-Castaneda, J. E. A. Landgrave and C. M. Gómez-Sarabia, "Conjugate phase plate use in analysis of the frequency response of imaging systems designed for extended depth of field", Appl. Opt. 47, E99 ? E105 (2008). CrossRef J. Ojeda-Casta-eda and Arturo Noyola-Isgleas, "High focal depth by apodization and digital restoration", Appl. Opt. 27, 2583-2586 (1988). CrossRef W. T. Cathey and E. R. Dowski, "New Paradigm for Imaging Systems", Appl. Opt. 41, 6080-6092 (2002). CrossRef J. Ojeda-Castaneda, E. Yépez-Vidal, E. García-Almanza and C. M. Gómez-Sarabia, "Tunable Gaussian mask for extending the depth of field", Photonics Letters of Poland, Vol. 4 (3), 115-117 (2012). DirectLink N. Brenner and C. Rader, "A new principle for fast Fourier transformation", IEEE Acoustics, Speech & Signal Processing 24, 264?266 (1976). CrossRef